LBP-Based Edge Detection Method for Depth Images With Low Resolutions - Xinyu Wang; Jie Cao; Qun Hao; Kaiyu Zhang; Zihan Wang; Saad Rizvi (IEEE Photonics Journal, 2019)
Depth edge represents contours of depth images. However, captured images often have low resolution. Furthermore, conventional edge detection methods fail to handle depth images with low resolution. To cater depth images with low resolution, we propose a novel edge detection method with high accuracy and computational speed. The proposed method modifies the local binary pattern and selects an adaptive threshold to obtain a rough edge map. Then, it removes irrelevant edges to obtain the result. Experimental results show that the proposed method can rapidly acquire accurate depth edge maps and is applicable to depth images with low resolution. The proposed method is compared with and outperforms other renowned edge detection methods.